RELATIONSHIP BETWEEN SELF-CONCEPT WITH MOTIVATION TO TEACH EARLY CHILDHOOD KADER POS IN SEMARANG - Nooruci Wirameiana; Tri Puji Astuti (Jurnal EMPATI, 2013)
National Education duty and responsibility to lead this nation in order to be ready to meet and compete with the era of globalization and changes into opportunities and then manage it into a force capable of improving the quality of life of the nation and the state in the future. Overview and assessment of the state kader of self in the present and future desires will influence the kader duties as an educator . Self-concept includes the assessment of the ability and inability kader of self- motivation that will affect the kader and play a role in determining the way in which kader in an attempt to reach our potential. The purpose of this study was to determine the relationship between self-concept and motivation to teach in early childhood kader post in Semarang .The population is 507 people and the total sample 157 kader. Using random sampling using sampling. Collecting data using Self-concept scale consisted of 20 aitem ( α = 0,86 ) and the Teaching Motivation Scale consists of 22 aitem ( α = 0,862 ). Statistical analysis of the data using simple regression.The results showed a positive and significant relationship between self-concept and motivation shown by the number of teaching correlation rxy = 0,742 with p = 0,000 ( p < 0,05 ) so that the hypothesis that a positive relationship between self-concept and motivation to teach the kader Post ECD in Semarang acceptable. It means that the relationship between the two variables is that the more positive self-concept, the higher the motivation to teach, otherwise the negative self-concept, the lower the motivation to teach. Effective contribution to the concept of teaching mmotivasi of 55,1 % , while 44,9 % is influenced by other factors, namely the state of psychological, social environment.